Politics and Security of Central and Eastern Europe : contemporary challenges (Cham, Switzerland: Springer, 2023)
This book analyzes major contemporary political and security problems in Central and Eastern Europe (CEE). Presenting case studies on various CEE countries, it highlights the persistence of non-democratic political trends in the region, with particular emphasis on authoritarianism in Belarus and the illiberal shift in the politics of Hungary and Poland. Also, the book examines the growing geopolitical and military rivalry between the West and Russia in the CEE region, which led to Russia's invasion of Ukraine. After addressing the increasing involvement of external entities such as NATO, the EU, the USA, Germany, France, and China, it highlights serious internal and external challenges to the democratic institutions and international security of CEE that call for new formats of multilateral cooperation to be established by the regions countries. This book is intended for scholars and students of European politics, international relations and security studies, and for anyone interested in the political and security challenges facing the CEE region.
Keywords: National Security -- Europe Central; National Security -- Europe Eastern